Gondolatok az erőforrás-szervezetről - Jánosi Bálint (Acta Universitatis Szegediensis : acta juridica et politica : publicationes doctorandorum juridicorum, 2007)
This essay is about one of the newest character of the Hungarian public procurement law: the source of power-organization. It examines the circumstances of its create, its rights, its obligations, its achievements of adoption compared to its purpose and the relation with the other procedure characters. The dissertation analyses the rules and the standpoints explained in the literature. Its subject is to find the solution to lawadapters' difficulties.